2006
DOI: 10.1038/nature05019
|View full text |Cite
|
Sign up to set email alerts
|

Highly ordered arrangement of single neurons in orientation pinwheels

Abstract: In the visual cortex of higher mammals, neurons are arranged across the cortical surface in an orderly map of preferred stimulus orientations. This map contains 'orientation pinwheels', structures that are arranged like the spokes of a wheel such that orientation changes continuously around a centre. Conventional optical imaging first demonstrated these pinwheels, but the technique lacked the spatial resolution to determine the response properties and arrangement of cells near pinwheel centres. Electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
274
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(295 citation statements)
references
References 30 publications
18
274
3
Order By: Relevance
“…2D; P Ͼ 0.1; Wilcoxon signedrank test). This result further supports the idea that response heterogeneity is not inconsistent with the precision of functional architecture (7,8).…”
Section: Materials and Methods)supporting
confidence: 78%
See 1 more Smart Citation
“…2D; P Ͼ 0.1; Wilcoxon signedrank test). This result further supports the idea that response heterogeneity is not inconsistent with the precision of functional architecture (7,8).…”
Section: Materials and Methods)supporting
confidence: 78%
“…Thus, two-photon calcium imaging studies have recently demonstrated that the functional architecture of orientation and direction selectivity in cat visual cortex (7,8) is extraordinarily precise. For instance, in area 18, neurons preferring opposite stimulus directions were segregated by remarkably specific ''fractures'' that were one to two cells wide (7).…”
mentioning
confidence: 99%
“…The situation is less clear, however, for other stimulus parameters, such as orientation. Gradual variation of stimulus orientation produces a gradual shift of orientation preference in numerous v1 subregions 60 , but these regions are separated by singularities (pinwheel centres) in which the orientation preference shifts abruptly [61][62][63] . This pattern is sometimes referred to as a mosaic-like map 64 .…”
Section: Maps and Modules In Primary Sensory Cortexmentioning
confidence: 99%
“…Here, we use regional imaging of intrinsic optical signals (IOSs) to define macroscopic remapping in somatosensory cortex of mice with targeted ischemic insults (Zhang et al, 2005;Schaffer et al, 2006;Brown et al, 2007;Zhang and Murphy, 2007). We then perform in vivo two-photon calcium imaging at different sites within these regional maps, as previously used in the visual and somatosensory cortex of unlesioned animals (Stosiek et al, 2003;Ohki et al, 2005Ohki et al, , 2006Kerr et al, 2007;Mrsic-Flogel et al, 2007;Sato et al, 2007;Winship et al, 2007). By optically recording neuronal activity using in vivo Ca 2ϩ imaging, we assessed stroke-induced changes in sensory-evoked function and spatial organization of Ͼ10,000 individual, visually identified cells in cortical layers 2/3.…”
Section: Introductionmentioning
confidence: 99%